Some Observations upon "Realistic" Trajectories in Bohmian Quantum Mechanics - María C. Boscá (Theoria, 2013)
Experimental situations in which we observe quantum effects that deviate from the intuitive expectations of the classical world call for an interdisciplinary discussion, and one fundamental issue to be considered is the compatibility between the description of phenomena and the assumption of an objective reality. This paper discusses the ontological interpretation of Bohmian quantum mechanics, focusing on the use of the term “trajectory” and the difficulties associated with its connection to a “real” (objective) trajectory. My conclusion is that the intended realistic interpretation of Bohmian trajectories is highly doubtful.